Enhanced anti-tumor efficacy by inhibiting HIF-1α to reprogram TAMs via core-satellite upconverting nanoparticles with curcumin mediated photodynamic therapy. (13th July 2021) - Zhang, Li-Jun; Huang, Rui; Shen, Yi-Wen; Liu, Jie; Wu, Ye; Jin, Jin-Mei; Zhang, Hong; Sun, Yun; Chen, Hong-Zhuan; Luan, Xin
Abstract : Cur–CSNPs mediated PDT suppress TNBC through the synergistic immunotherapeutic effects by suppressing the expression of HIF-1α to reprogram the pro-tumor TAM2 into the anti-tumor TAM1. Abstract : Tumor hypoxic stress after photodynamic therapy (PDT) will be inevitably exacerbated by the vascular blocking effects and oxygen consumption in the tumor microenvironment (TME) which usually leads to compromised efficacy and clinical performance. Increasing evidence links the hypoxia induced up-regulation of hypoxia inducible factor 1α (HIF-1α) with immunosuppressive TME, including the polarization of M2 phenotype tumor associated macrophages (TAMs), which promote the recurrence and metastasis. Here, we reported NIR-triggered core-satellite upconverting nanoparticles (CSNPs) with curcumin (Cur) embedded as a difunctional photosensitizer, which could realize PDT in deep tumors with long excitation wavelength (980 nm) and reverse the immunosuppressive TME induced by up-regulated HIF-1α at the same time. This Cur-loaded CSNPs (Cur–CSNPs)-mediated PDT could successfully induce the immunogenic cell death (ICD) of triple negative breast cancer (TNBC) cell lines (4T1 and MDA-MB-231) in vitro and repolarize the 4T1 cells co-cultured TAMs from pro-tumor M2 to the anti-tumor M1 phenotype. Furthermore, Cur–CSNPs-mediated PDT could suppress the 4T1 tumor growth in primary and distant sites through the synergistic immunotherapeutic effects in vivo by priming M1 type TAMs and CD4 + /CD8 + T cells' infiltration. Our data highlight the novel application of CSNPs-embedded Cur as a difunctional photosensitizer to enhance the anti-tumor efficacy of PDT.